Kaposi sarcoma among people living with HIV in the French DAT'AIDS cohort between 2010 and 2015. (30th April 2020) - Poizot‐Martin, I.; Obry‐Roguet, V.; Duvivier, C.; Lions, C.; Huleux, T.; Jacomet, C.; Ferry, T.; Cheret, A.; Allavena, C.; Bani‐Sadr, F.; Palich, R.; Cabié, A.; et al.
Abstract: Background: Although antiretroviral therapy (ART) has reduced the risk of Kaposi sarcoma (KS), KS cases still occur in HIV‐infected people. Objective: To describe all KS cases observed between 2010 and 2015 in a country with high ART coverage. Methods: Retrospective study using longitudinal data from 44 642 patients in the French Dat'AIDS multicenter cohort. Patients' characteristics were described at KS diagnosis according to ART exposure and to HIV‐plasma viral load (HIV‐pVL) (≤50 or >50) copies/mL. Results: Among the 209 KS cases diagnosed during the study period, 33.2% occurred in ART naïve patients, 17.3% in ART‐experienced patients and 49.5% in patients on ART, of whom 23% for more than 6 months. Among these patients, 24 (11.5%) had HIV‐pVL ≤50 cp/mL, and 16 (66%) were treated with a boosted‐PI‐based regimen. The distribution of KS localization did not differ by ART status nor by year of diagnosis. Limitations: Data on human herpesvirus 8, treatment modalities for KS and response rate were not collected. Conclusion: Half of KS cases observed in the study period occurred in patients not on ART, reflecting the persistence of late HIV diagnosis. Factors associated with KS in patients on ART with HIV‐pVL ≤50 cp/mL remain to be explored.